Labour Supply Implications of a Negative Income Tax Plan - Roy, Arun (Relations industrielles / Industrial Relations, 1979)
This study demonstrates that a Negative Income Tax Plan can be expected to result in fairly large reductions in the supply of work effort in the case of younger workers. The potential reductions in labour supply of female workers appear to be particularly large.